2020
DOI: 10.3389/fmicb.2020.01553
|View full text |Cite
|
Sign up to set email alerts
|

Increased Antibody Response to Fucosylated Oligosaccharides and Fucose-Carrying Bacteroides Species in Crohn’s Disease

Abstract: Inflammatory bowel disease is associated with intestinal dysbiosis and with elevated antibody production toward microbial epitopes. The underlying processes linking the gut microbiota with inflammation are still unclear. Considering the constant induction of antibodies by gut microbial glycans, the aim of this study was to address whether the repertoire of carbohydrate-specific antibodies is altered in Crohn's disease or ulcerative colitis. IgG and IgM reactivities to oligosaccharides representative of mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Interestingly, 5 of the 16 genes that regulate IgG glycosylation contain SNPs linked to increased risk for IBD identified by GWAS 39 . Reduced levels of serum IgG sialylation is observed in both UC and Crohn’s disease 112 114 as well as altered fucosylation, with increased levels detected in Crohn’s disease and lower levels in people with UC 112 , 115 . While the functional role of IgG fucosylation in regulating intestinal inflammation is not understood, afucosylated IgG has been shown to enhance pro-inflammatory cytokine production by monocytes in the lungs of individuals with severe COVID-19 116 , suggesting that altered IgG fucosylation could also contribute to IBD pathobiology.…”
Section: Igg Glycosylation and Effector Function Alterations In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 5 of the 16 genes that regulate IgG glycosylation contain SNPs linked to increased risk for IBD identified by GWAS 39 . Reduced levels of serum IgG sialylation is observed in both UC and Crohn’s disease 112 114 as well as altered fucosylation, with increased levels detected in Crohn’s disease and lower levels in people with UC 112 , 115 . While the functional role of IgG fucosylation in regulating intestinal inflammation is not understood, afucosylated IgG has been shown to enhance pro-inflammatory cytokine production by monocytes in the lungs of individuals with severe COVID-19 116 , suggesting that altered IgG fucosylation could also contribute to IBD pathobiology.…”
Section: Igg Glycosylation and Effector Function Alterations In Ibdmentioning
confidence: 99%
“…Overall, a clear functional role for IgG glycosylation in IBD pathophysiology has yet to be determined. However given that current strategies for differential diagnosis and monitoring of IBD can lack sensitivity and are often invasive 122 , 123 , measurement of serum IgG glycosylation could potentially represent an attractive and minimally invasive option for IBD patient stratification 114 , 115 .…”
Section: Igg Glycosylation and Effector Function Alterations In Ibdmentioning
confidence: 99%
“…These antibodies recognize oligosaccharides that are frequently found on the surface of gut microbes, such as laminaribioside, laminarin, mannobioside, chitobioside, and chitin [ 190 193 ]. In our own studies, we observed an increased antibody response to carbohydrates in blood serum of patients with Crohn’s disease compared with healthy controls, which was mainly reflected by a higher antibody reactivity to fucosylated oligosaccharides and could be linked to increased antibody recognition of intestinal Bacteroides species [ 194 ]. Given the association between intestinal dysbiosis and altered anti-bacterial antibodies, the question arises whether these antibodies targeting bacterial antigens contribute to the etiology of inflammatory bowel disease.…”
Section: Autoimmunitymentioning
confidence: 99%
“…This can indicate the active degradation of mucins. At the same time, many glycans have the same composition, but clearly differ structurally; therefore, the study of their structure is of interest from the viewpoint of the patterns they form [ 246 ]. The role of 1,2-Fuc–containing patterns is not clear.…”
Section: Discussionmentioning
confidence: 99%